The Relationship Between Recruitment and Selection Practices and Employee Performance: A Study at The Margaya Community Health Center an Majalengka - Fadjar Tri Sakti (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Recruitment and selection of human resources are crucial factors in ensuring the quality of public services, particularly within primary health care. The urgency of this study arises from the case of Puskesmas Margaya Majalengka, where employee performance is closely linked to recruitment and selection mechanisms that still face challenges of transparency and competency alignment. This research aims to analyze the relationship between recruitment and selection practices and employee performance, drawing on Human Capital, Person-Job Fit, and Merit System theories. The study employs a qualitative case study approach, utilizing in-depth interviews, observation, and document analysis. The findings reveal that non-merit-based recruitment and selection lead to decreased productivity, mismatched placement, and reduced service quality. The discussion highlights that strengthening competency-based recruitment and selection systems is essential for improving the quality of health services at the primary level.